Exposure to biomass smoke induces pulmonary Th17 cell differentiation by activating TLR2 on dendritic cells in a COPD rat model. (15th September 2021) - Pu, Jinding; Xu, Juan; Chen, Lu; Zhou, Hongbin; Cao, Weitao; Hao, Binwei; Li, Naijian; Wu, Jianxiong; Zheng, JinZhen; Hong, Wei; Li, Bing; Ran, Pixin
Highlights: Biomass smoke (BS) induces Th17 responses in rats. IL-17A is required for BS-induced emphysema. Lung dendritic cells (DCs) from BS-exposed rats induce IL-17A expression ex vivo . BS-related particulate matter (BRPM) activates DCs from bone marrow in vitro . BRPM-exposed bone marrow-derived DCs induce Th17 differentiation via TLR2. Abstract: Almost three billion people in developing countries are exposed to biomass smoke (BS), which predisposes them to developing chronic obstructive pulmonary disease (COPD). COPD is associated with abnormal innate and adaptive immune responses in the lungs and systemic circulation, but the mechanisms underlying BS-COPD development are uncertain. We investigated the role of dendritic cells (DCs) and interleukin (IL)-17A in BS-COPD. We investigated T helper cell responses in the BS-exposed COPD rat model by flow cytometry, quantitative PCR, and enzyme-linked immunosorbent assays. We conducted ex vivo experiments to determine which antigen-presenting cells induce Th17 cell responses. We evaluated the in vitro effects of BS-related particulate matter (BRPM) (2.5 μm) on the function of bone marrow-derived dendritic cells (BMDCs). We found that BS exposure enhanced Th17 responses in the lungs of the COPD-modelled rats, and the stimulated DCs (but not the macrophages) were sufficient to induce naïve CD4 + T cells to produce IL-17A in ex vivo experiments. BRPM significantly enhanced the maturation and activation of DCs through Toll-like receptor 2 (TLR2), but not TLR4, and induced Th17 responses. Therefore, BS activated lung DCs through TLR2, which led to Th17 responses and emphysema in the rats. This process is possibly therapeutically targetable.